Kritik Sosial dalam Geguritan â€œDunga Munggah Pangkatâ€ Karya Budi Palopo - Qothrunnada, Nur Malisa; Sulanjari, Bambang (Program Studi Pendidikan Bahasa dan Sastra Daerah, 2023)
The purpose of making this article is to find out the incompatibility of the work of Javanese literature on Geguritan Budi Palopo with the title